Monumental landscapes and the agency of the dead along the Murray River, Australia. Issue 1 (1st January 2020) - Littleton, Judith; Allen, Harry
ABSTRACT: Using a surviving record from AD 1856/7, we analyse the distribution of Aboriginal burial monuments along the Murray River, Australia recorded by Gerard Krefft and William Blandowski. Their detailed record enables us to recreate a necrogeography along the river. The regional perspective this provides demonstrates both broad traditions and clinal shifts that serve to identify zones of diversity and interaction. These zones of practice were recognized by Aboriginal and non-Aboriginal people who reacted to them in structured ways that recognized the temporality of the sites and sequences. Since 1857, the above-ground architecture of these monuments has disappeared; however, they continue to exist as burial mounds or eroded features where single or multiple Aboriginal burials are apparent. While memory of the original burial architecture has faded, the remnants have re-emerged in the recent past as key places within debates about colonialism and genocide. We argue that within this changing necrogeography, the dead have an effective agency, one that is partial, complex and the result of an interaction between the specific perceptions of the viewer and the dead themselves.